2000
DOI: 10.1021/ja994066+
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Aminobenzonitrile Isomers by a Diol Host Compound:  Structure and Selectivity

Abstract: 1,1,6,6-Tetraphenylhexa-2,4-diyne-1,6-diol (H) forms inclusion compounds with 2-, 3-, and 4-aminobenzonitrile (2ABN, 3ABN, and 4ABN). In each case the host:guest ratio is 1:2 and the structures are stabilized by hydrogen bonds. Competition experiments show that the host selects the guests in order of preference of 2ABN > 3ABN > 4ABN. These results are in general agreement with lattice energy calculations, thermal analyses, and solid-state reactions. The structure of the solid formed between H and a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…The study of the influence of the solvent 50 -52 has been pointed out as important, because it has been reported that the ICT process does not take place with aminoBN in alkane solvents. 53 Complexes of 4ABN with 4-aminobenzoic acid 54 and other compounds 55 have also been reported. The cationic form of 4ABN has been studied by twocolor R2PI spectroscopy and ab initio methods.…”
Section: Introductionmentioning
confidence: 87%
“…The study of the influence of the solvent 50 -52 has been pointed out as important, because it has been reported that the ICT process does not take place with aminoBN in alkane solvents. 53 Complexes of 4ABN with 4-aminobenzoic acid 54 and other compounds 55 have also been reported. The cationic form of 4ABN has been studied by twocolor R2PI spectroscopy and ab initio methods.…”
Section: Introductionmentioning
confidence: 87%
“…In fact we are aware of only one such study: Caira et al reported the selectivity behaviour of an organic host molecule (1,1,6,6tetraphenylhexa-2,4-diyne-1,6-diol) towards 2-, 3-and 4-aminobenzonitrile. 12 The authors reported similar selectivity profiles from solution and solid-state methods for two solvents, and somewhat different selectivity profiles for the third solvent. The authors comment that the mechanochemical reactions 'follow the trends obtained in the solution experiments'.…”
mentioning
confidence: 90%
“…The authors comment that the mechanochemical reactions 'follow the trends obtained in the solution experiments'. 12 Our combined interest in the host-guest chemistry of pamoate salts, and in mechanochemistry, led us to further investigate the selectivity behaviour of a new pamoate-based host system, 1,10-phenanthrolinium pamoate (1, Scheme 1) using mechanochemistry.…”
mentioning
confidence: 99%
“…This process is effective for a range of substrates in uniformly high enantiomeric excess. Further work from the same group [19][20][21][22] has Scheme 1 Enantioselective photoreaction of a tropolone ether in a crystalline inclusion complex. followed in which the structures of the inclusion complexes have been studied by X-ray crystallography, the range of substrates extended with yields as high as 70%, with up to 98% ee.…”
Section: Anthony G Coynementioning
confidence: 99%